Gangguan Bermain Game Selama Pandemi Covid-19: Sebuah Tinjauan Pustaka Sistematis - Pranaya, Astaf Aji; Sarjani, Dini Kumalawati; Rosalia, Fanny; Shabrina, Rahma Mesi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The COVID-19 pandemic has had a broad global impact, including fear of disease and the lockdown situation. This situation has led to a significant increase in interest in various forms of digital entertainment, especially online games. The high number of online game users provides many benefits, but it also creates the problem of gaming interruption. This study aims to comprehensively explain the factors that influence gaming disorder and the impact it causes using a systematic literature review method of 60 research journal articles indexed by Scopus. From the results of this study, it was found that several factors influence gaming disorder, including feelings of loneliness, boredom, feelings of loss of meaning in life, low self-compassion, stress, increased playing time, and psychological comorbidities. Meanwhile, gaming disorder also has a physical impact, which causes a decrease in the quality of life of individuals, such as the emergence of sleep disturbances and insomnia, affecting individual basic needs such as eating and personal hygiene, obsessive characteristic psychological disorders, and even reducing empathy. In addition, changes in the education system where schools are held online give students a lot of free time, resulting in increased aggressive behavior among them. Early detection of factors that influence gaming disorder requires family support and supervision. This has implications for prevention and early intervention for policymakers and game developers.